The impact of the excessive daytime sleepiness on population safety on traffic roads and at work places - Todea, Doina; Herescu, Andreea; Roşca, Loredana (Medicine and Pharmacy Reports, 2011)
Excessive daytime sleepiness (EDS) is a matter of public interest with medico-legal implications when subjects with excessive daytime sleepiness present decreased ability to work, low work productivity, or, even worse, workplace accidents or motor vehicle accidents. The main symptom of obstructive sleep apnoea syndrome (OSA) is excessive is daytime sleepiness. OSA is characterized by obstructive events of upper airways during sleep . OSA increases the risk of car accidents by 3.71 to 7 times, doubles the risk of workplace accidents, decreases employee performance with increasing days of sick leave. Appropriate treatment, represented by continuous positive pressure therapy – CPAP – significantly reduces the risk of car accidents or workplace accidents and increases productivity and performance of patients. All those with excessive daytime sleepiness, impaired concentration or memory that are performing activities that endanger public safety (e.g. professional drivers) should be referred to a sleep laboratory for diagnosis of sleep-related breathing disorders and for establishment of an appropriate treatment.